2004
DOI: 10.1093/toxsci/kfh013
|View full text |Cite
|
Sign up to set email alerts
|

2,3,7,8-Tetrachlorodibenzo-p-dioxin (TCDD) Alters the Regulation of Pax5 in Lipopolysaccharide-Activated B Cells

Abstract: The environmental contaminant 2,3,7,8-tetrachlorodibenzo-p-dioxin (TCDD) produces a profound suppression of the primary immunoglobulin-M (IgM) antibody response. The suppression of IgM production by TCDD can occur through direct interactions with the B cell, is aryl hydrocarbon receptor-dependent, and is mediated through alterations in the differentiation of B cells into plasma cells. The objective of the present investigation was to characterize the effects of TCDD on the regulation of Pax5, a crucial repress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
35
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(44 citation statements)
references
References 30 publications
8
35
1
Order By: Relevance
“…ITE may mainly affect B cell differentiation into Igsecreting plasma cells by suppressing the expression of XBP-1 at the transcriptional level, but its precise mode of action remains elusive. Some papers have reported that TCDD treatment impaired the downregulation of Pax5, which is a repressor of B cell differentiation and a transcriptional repressor of XBP-1 (21,24). In contrast, we observed that there was no change in the expression of Pax-5 mRNA in ITE-treated mouse B cells.…”
Section: Effects Of Ahr Ligands On Plasma Cell Differentiation Of Moucontrasting
confidence: 82%
“…ITE may mainly affect B cell differentiation into Igsecreting plasma cells by suppressing the expression of XBP-1 at the transcriptional level, but its precise mode of action remains elusive. Some papers have reported that TCDD treatment impaired the downregulation of Pax5, which is a repressor of B cell differentiation and a transcriptional repressor of XBP-1 (21,24). In contrast, we observed that there was no change in the expression of Pax-5 mRNA in ITE-treated mouse B cells.…”
Section: Effects Of Ahr Ligands On Plasma Cell Differentiation Of Moucontrasting
confidence: 82%
“…However, little is known about the mechanism by which TCDD-mediated suppression of B cell differentiation occurs and what other aspects of B cell differentiation, besides the IgM response, are affected by TCDD treatment. In previous studies, TCDD treatment of LPS-activated CH12.LX cells was shown to markedly reduce the mRNA levels of IgH, Ig, and IgJ as well as protein levels of XBP-1 (Yoo et al, 2004). In activated B cells treated with TCDD, Pax5 mRNA and protein levels remained abnormally elevated, and they also maintained abnormally high DNA binding activity as identified in nuclear extracts (Yoo et al, 2004).…”
Section: Introductionmentioning
confidence: 90%
“…In previous studies, TCDD treatment of LPS-activated CH12.LX cells was shown to markedly reduce the mRNA levels of IgH, Ig, and IgJ as well as protein levels of XBP-1 (Yoo et al, 2004). In activated B cells treated with TCDD, Pax5 mRNA and protein levels remained abnormally elevated, and they also maintained abnormally high DNA binding activity as identified in nuclear extracts (Yoo et al, 2004). In addition to transcriptional regulation, the expression of Pax5 can be modulated by mechanisms involving post-transcriptional modifications (Zwollo et al, 1997;Lin et al, 2002).…”
mentioning
confidence: 89%
“…Removal of protein binding to the DRE and B sites may alter DNA binding or protein-protein interactions of transcription factors with affinity for these flanking DNA motifs. Additionally, TCDD has been shown to alter the regulation and expression of Pax5/BSAP in LPS-stimulated CH12.LX cells (Yoo et al, 2004). Specifically, TCDD maintains the expression of BSAP, which is typically down-regulated during B cell differentiation into plasma cells.…”
Section: Downloaded Frommentioning
confidence: 99%